Education and Learning in the 21st Century: An Emergency Agenda for Sustainable Development - Siqueira, Ivan (Mediterranean Journal of Social Sciences, 2012)
The 21st Century has observed an increase transformation on the basis of economy and social patterns. Thechallenging of education is now prepared for the future, not for the present. The changing environment oflearning is related to competencies and skills rather than in particular subjects and theories. How to teachwhat is not present yet? Why education must be profoundly related both to Information andCommunication Technology and human ethnic? This paper is dedicated to highlight some of these points,bringing some reflections regarding these topics about the relationship between Africa and Latin America,especially Brazil.